Molecular Diagnostic Assay for Rapid Detection of Flag Smut Fungus (Urocystis agropyri) in Wheat Plants and Field Soil - Kashyap, Prem Lal; Kumar, Sudheer; Kumar, Ravi Shekhar; Sharma, Anju; Jasrotia, Poonam; Singh, Devendra Pal; Singh, Gyanendra Pratap (Frontiers in Plant Science, 2020)
Flag smut incited by Urocystis agropyri has the potential to cause substantial reduction in yield and quality of wheat production. An early and precise diagnosis is a key component in the successful management of flag smut of wheat. Therefore, a simple molecular assay for the rapid detection of U. agropyri was developed for the first time. To detect U. agropyri, species specific primers were developed by comparing the partial sequences of internal transcribed spacer (ITS) DNA region of U. agropyri with related and unrelated phytopathogenic fungi. The clear amplicons of 503 and 548 bp were obtained with the two sets of designed primers (UA-17F/UA-519R and UA-15F/UA-562R) from the genomic DNA of 50 geographic distinct isolates of U. agropyri. However, no amplicon was obtained from the DNA of other 21 related and unrelated phytopathogenic fungi which showed the specificity of the primers for the U. agropyri. PCR reaction was also set up to confirm the presence of U. agropyri spores in six different wheat varieties along with eleven distinct regional soil samples as template DNA. The presence of U. agropyri in all the soil samples collected from an infected field and plant tissue of diseased plants collected at two different stages (20 and 40 days post sowing) and the absence in the soils and plants of healthy plots indicated 100% reliability for detection of U. agropyri. This simple and rapid test can be employed for the detection of U. agropyri from enormous wheat and soil samples in very short time with less man power. Thus, the reported molecular assay is very specific for U. agropyri and requires less time and man power over conventional diagnosis which is often confused by coinciding morphological features of closely related fungal pathogens, and therefore, it can be used for quarantine surveillance of flag smut.